Bourdieu's habitus clivé in voicing, feeling, being Aboriginal. (June 2023) - Andrews, Julie; Burns, Edgar; James, Claire; Rajčan, Adam
Bourdieu's concept of habitus clivé is discussed in relation to Aboriginal Australians' experience within dominant White society. The argument is put forward that the concept can make an important contribution to illuminating Indigenous experience. At the same time there is an ever-present danger that habitus clivé becomes another tool for theorising about Aboriginal people, even if sympathetically, rather than a vehicle for Aboriginal expression of history, pain, suffering and contemporary aspirations. Growing recognition of the value of Aboriginal culture, art and ways of knowing is desirable and a positive part of present shifts in Australian cultural identities. Changing cultural tastes and an aesthetic sense beyond co-option of place involves telling and re-telling many difficult stories with Aboriginal experiences at the centre and learning to embrace what we hear.